Gold catalysed site-selective cross-coupling of tertiary α-silylamines with 1-iodoalkynes under UVA LED light. Issue 3 (23rd December 2022) - Zhao, Yichao; Merrett, James Theodore; Jin, Jianwen; Yu, Li-Juan; Coote, Michelle Louise; Chan, Philip Wai Hong
Abstract : A synthetic method that relies on a gold(i, i ) complex and UVA LED light source to catalyse the α-alkynylation of tertiary α-silylamines by 1-iodoalkynes is described. Abstract : A synthetic method that relies on [Au2 (μ-dppm)2 ]Cl2 (dppm = bis(diphenylphosphino)methane) and UVA LED (LED = light emitting diode) light ( λ = 365 nm) to mediate the α-alkynylation of tertiary α-silylamines by 1-iodoalkynes is described. The site-selective desilylative C(sp 3 )–C(sp) bond formation protocol was demonstrated to exhibit excellent functional group tolerance as it was applicable to a broad range of coupling partners and a variety of bioactive molecules and natural products. Experimental and computational studies suggest the reaction mechanism follows an oxidative quench pathway that generates the two surmised radical species of the amine and alkyne substrates. It also implied the possible involvement of the dimeric metal complex in mediating the ensuing cross-coupling of the two radical species, which is unprecedented in photoredox gold(i, i ) catalysis.